Paronomasia in Raditya Dika's Podcast Tidak Akan Ada Agak Laen 2 on YouTube: A Semantic Study - Andini Dara Ananti (Raja Zulkarnain Education Foundation, 2026)
This study aims to describe the forms of paronomasia in Raditya Dika’s podcast entitled “Tidak Akan Ada Agak Laen 2” through an analysis of meaning relations in semantic studies. Paronomasia is understood as a language game or word twists, so it is relevant to be studied in the context of podcasts that are spontaneous, interactive, and full of improvisation. The data sources for this study include all utterances produced by Raditya Dika and other comedians in the podcast, while the data are in the form of utterance units that show sound similarities accompanied by shifts in meaning. Data collection was carried out through observation and recording techniques using observation sheets to record, select, and identify forms of word twists in the context of conversation. Data analysis includes data reduction, classification of forms of meaning relations, analysis of the context of emergence, and presentation of results in a qualitative descriptive manner. The results of the study indicate that paronomasia is realized through three main forms of meaning relations, namely acronyms, homophony, and paronymy. Acronyms are found in two data in the form of creative shortenings, namely “ela” and “gaukat”. Homophony is the most dominant form, characterized by sound similarities that produce different meanings, as seen in the use of “tortor”, “pabrik gulai”, “pim-pim”, and “sunglap”. Paronymy is identified through puns on the film titles “Sabtu Bersama Batak”, “Perempuan Tanah Jahe Enam”, and “Kambing Santan”. The research findings indicate that paronomasia functions as a linguistic strategy that utilizes phonological creativity and meaning-relational mechanisms to construct humor while maintaining interaction in digital spoken discourse. Theoretically, this research strengthens understanding of the role of paronomasia in the process of meaning-formation in podcast-based communication.